2009
DOI: 10.1021/jp810205a
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Study and First-Principles Calculations of the Interaction between Nucleic Acid Bases and Carbon Nanotubes

Abstract: In this work, we have used Raman spectroscopy and quantum chemical methods (MP2 and DFT) to study the interactions between nucleic acid bases (NABs) and single-walled carbon nanotubes (SWCNT). We found that the appearance of the interaction between the nanotubes and the NABs is accompanied by a spectral shift of the high-frequency component of the SWCNT G band in the Raman spectrum to a lower frequency region. The value of this shift varies from 0.7 to 1.3 cm(-1) for the metallic nanotubes and from 2.1 to 3.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 23 publications
12
41
0
Order By: Relevance
“…The conclusion is based on comparison of the energies obtained by ab initio calculation. In accordance with these calculations, the stacking energy of the adenine dimer is not more than 9 kcal/mol [25], but the energy of p-p stacking between adenine and SWNT (10.0) is 14 kcal/mol [26]. Thus, we believe that the main contribution to the temperature dependence of the hyperchromic coefficient is made with residual selfstacking polymer fragments.…”
Section: Uv-vis Spectroscopy Of Nanohybrid Formed By Homopolynucleotisupporting
confidence: 79%
“…The conclusion is based on comparison of the energies obtained by ab initio calculation. In accordance with these calculations, the stacking energy of the adenine dimer is not more than 9 kcal/mol [25], but the energy of p-p stacking between adenine and SWNT (10.0) is 14 kcal/mol [26]. Thus, we believe that the main contribution to the temperature dependence of the hyperchromic coefficient is made with residual selfstacking polymer fragments.…”
Section: Uv-vis Spectroscopy Of Nanohybrid Formed By Homopolynucleotisupporting
confidence: 79%
“…For geometry optimization and subsequent interaction energy calculations, we have selected Truhlar's M05-2X 39 functional and the 6-31G++(2d,2p) basis set 40 . M05-2X is a hybrid meta GGA functional with 56% Hartree-Fock exchange component and is known to perform remarkably well for noncovalently bonded molecules of biological relevance, 41 including nucleobases [42][43][44][45][46][47][48][49] . 6-31G++(2d,2p) is a split valance double ζ type basis set, with two sets of d type polarization function for all non-hydrogen atoms and two sets of p type polarization function for hydrogen atoms, and also include s-p diffused orbitals for non-hydrogen atoms, was used for ground state geometry optimization.…”
Section: Tools and Methodsmentioning
confidence: 99%
“…This work initiated the studies on the noncovalent functionalization of carbon nanotubes. Now several reports are available about the noncovalent functionalization of CNT with biological molecules like DNA 9–14, amino acids 15, and proteins 16. These studies have received considerable research interest because the electronic and mechanical properties of the CNT remain unaltered after functionalization 17.…”
Section: Introductionmentioning
confidence: 99%
“…Gowtham et al 12 reported the binding strength of DNA and RNA nucleic acid bases with CNT (5,0) and the direct correlation with the molecular polarizabilities of the base molecules. Interactions of nucleic acid bases with carbon nanotube (10,0) and with planar graphene surface were examined using a Raman spectroscopic technique and quantum‐chemical methods with different functionals 13. The Raman studies have shown a spectral down shift of the high‐frequency component of the G band of the SWCNTs.…”
Section: Introductionmentioning
confidence: 99%